The intronic ABCA4 c.5461‐10T>C variant, frequently seen in patients with Stargardt disease, causes splice defects and reduced ABCA4 protein level. Issue 3 (24th October 2016) - Aukrust, Ingvild; Jansson, Ragnhild W.; Bredrup, Cecilie; Rusaas, Hilde E.; Berland, Siren; Jørgensen, Agnete; Haug, Marte G.; Rødahl, Eyvind; Houge, Gunnar; Knappskog, Per M.
Abstract: Purpose: Despite being the third most common ABCA4 variant observed in patients with Stargardt disease, the functional effect of the intronic ABCA4 variant c.5461‐10T>C is unknown. The purpose of this study was to investigate the molecular effect of this variant. Methods: Fibroblast samples from patients carrying the ABCA4 variant c.5461‐10T>C were analysed by isolating total RNA, followed by real‐time polymerase chain reaction (RT‐PCR) using specific primers spanning the variant. For detection of ABCA4 protein, fibroblast samples were lysed and analysed by SDS‐PAGE followed by immunoblotting using a monoclonal ABCA4 antibody. Results: The ABCA4 variant c.5461‐10T>C causes a splicing defect resulting in the reduction of full‐length mRNA in fibroblasts from patients and the presence of alternatively spliced mRNAs where exon 39–40 is skipped. A reduced level of full‐length ABCA4 protein is observed compared to controls not carrying the variant. Conclusions: This study describes the functional effect and the molecular mechanism of the pathogenic ABCA4 variant c.5461‐10T>C. The variant is functionally important as it leads to splicing defects and a reduced level of ABCA4 protein.